Pemberdayaan Ekonomi Kreatif Melalui Pendampingan Praktisi Usaha Dalam Penguatan Jiwa Kewirausahaan Siswa SMK - Puput Erna Sari; Jesika Melina Simamora (Jurnal Pengabdian Cita Masyarakat, 2025)
This community service initiative aims to enhance the entrepreneurial spirit of students at SMKN 1 Jorlang Hataran through mentoring by creative business practitioners. Utilizing Participatory Action Research (PAR) and experiential learning theory, the program engaged twenty students in "creative bucket" production. Interventions included technical product manufacturing training, cost of goods sold (COGS) calculation, and digital marketing strategies. Results demonstrate significant improvements in students' psychomotor competencies and financial literacy, evidenced by the successful production of market-ready goods. However, the transition to independent entrepreneurship still faces structural hurdles such as initial capital availability, low self-efficacy, and limited long-term mentoring. This study concludes that collaboration between academia and practitioners adds substantial value to vocational curricula. To ensure sustainability, the implementation of a Teaching Factory (TEFA) model and access to school micro-capital are recommended to create a resilient entrepreneurial ecosystem. Continuous synergy is essential to produce adaptive graduates facing global economic dynamics in Simalungun.